Pengaruh Media Sosial, Pembelajaran Daring, dan Kecerdasan Emosional Terhadap Etika dan Perilaku Taruna Pelayaran - Janny Adriani Djari; Mohammad Sapta Heriyawan (Politeknik Ilmu Pelayaran Semarang, 2022)
Technology in the digitalization era and the Covid-19 pandemic has changed systems and patterns of life, including character education for cadets. Digital era has brought various good changes as a positive impact that can be used as well as possible. But at the same time, digital era also brings many negative impacts, so that it becomes a new challenge in human life in this digital era, especially for the Level I cadets of the PIP Semarang. The purpose of this study was to analyze the effect of the digitalization era as proxied as social media, online learning and emotional intelligence on the ethics and behavior of Level I cadets of PIP Semarang. The method used in this research is quantitative. The population in this study was 412 cadets, while the sample was 274 cadets. Data analysis used multiple linear regression. The F test in this study indicate that social media, online learning and emotional intelligence together affect the ethics and behavior of the Level I cadets of PIP Semarang. Based on this research, it can be concluded that the digitalization era has an effect on the ethics and behavior of Level 1 cadets at PIP Semarang.